Prevalence of methicillin resistance in Staphylococcus pseudintermedius isolates from dogs with skin and ear infections in South Africa - Leisewitz, Andrew L. (University of Pretoria, 2022)
Dissertation (MSc (Veterinary Science))--University of Pretoria, 2021.